Pengaruh Rasio Likuiditas, CAR dan NPM Terhadap Pertumbuhan Laba Pada Perusahaan Perbankan - Gina Amalia Firdaus (Jurnal Ilmu Akuntansi, 2021)
This study aims to determine the effect of Liquidity Ratio, CAR and NPM on Profit Growth of Banking Companies. The variables in this study are Liquidity Ratio, CAR, NPM and Profit Growth. The method used in this study is a quantitative method with an associative approach. By using secondary data. The population in this study is a state-owned bank listed on the Indonesia Stock Exchange. The sample used in the study was determined by purposive sampling method and obtained 36 data on the financial statements of state-owned banks that met the criteria. The data analysis techniques used are: 1) Classical assumption test 2) Hypothesis Testing. The results of this study indicate that the hypothesis test with a t-value oftable 2.036 that the liquidity ratio (LDR) variable has a t-valuecount of -3.325 (-3.325<2.036) which means partially LDR has no effect on profit growth. The variable (CAR) has a t-valuecount of 0.784 or (0.784 <2.036) which means that partially the CAR variable has no effect on profit growth. Variable (NPM), the value of tcount is 2.534 or (2.534> 2.036) which means that the NPM variable has an effect on profit growth. And with the results of the analysis of the f test obtained ftable of 2.90 and the value of fcount of 4.278 which means that fcount is greater than ftable or (4.278> 2.90) with a sig value of 0.012 <0.05 which means simultaneously independent variables effect on the dependent variable, so it can be concluded that together there is the efferct between the liquidity ratio, CAR and NPM on profit growth.